2003
DOI: 10.1007/s00595-003-2611-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Subtotal Colectomy with Antiperistaltic Cecoproctostomy

Abstract: Subtotal colectomy with our new CRA technique is appropriate for treating inflammatory diseases of the bowel, colon tumors, and intractable constipation in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…A US nationwide dataset derived from hospital episode statistics was also included covering 2377 procedures coded as colectomy for constipation indications [19]. Specific exclusions after full-text review (and after exclusion of non-English language publications: n = 10) included 27 studies where the population sample was confirmed to be less than 20 patients, four studies of out of scope procedures, one study where data were considered duplicate [13], one where outcomes could not be segregated by eligible procedure [14], and one where data for multiple clinical indications for colectomy were merged [15]. [27] 1995 Cleveland Clinic, FL USA 54 27 RCS IV Redmond [21] 1995 John Hopkins, Baltimore USA 34 90 PCH IIB de Graaf [28] 1996 Rotterdam Netherlands 42 46 PCH IV Lubowski [29] 1996 Sydney Australia 52 42 RCS IV Platell [30] 1996 Perth Australia 96 60 RCS IV Pluta [31] 1996 Alberta Canada 24 65 RCS IV Ghosh [32] 1996 Edinburgh UK 21 96 RCS IV Nyam [33] 1997 Singapore Singapore 74 56 PCH IV Ho [34] 1997 Singapore Singapore 24 24 RCH IV You [35] 1998 Taiwan China 40 24 PCS IV Bernini [36] 1998 Mayo Clinic, MN USA 106 78 RCH IV Hasegawa [37] 1999 Birmingham UK 61 84 RCH IV Fan [38] 2000 Taiwan China 24 23 RCS IV Pikarsky [39] 2001 Cleveland Clinic, FL USA 62 105 RCH IV Pikarsky [40] 2001 Cleveland Clinic, FL USA 30 60 PCS IV Webster & Dayton [41] 2001 Cancun Mexico 50 12 RCS IV Mollen [42] 2001 Bennekom Netherlands 21 62 PCS IV Nylund [43] 2001 Goteburg Sweden 40 132 PCS IV Lundin [44] 2002 Uppsala Sweden 28 50 PCS IV Fitzharris [45] 2003 Mayo Clinic, MN USA 75 47 RCS IV Hassan [46] 2006 Mayo Clinic, MN USA 104 68 RCH IV Marchesi [47] 2007 Parma Italy 23 72 PCS IV Zutshi [48] 2007 Cleveland Clinic, OH USA 69 130 RCS IV Feng [22] 2008 Zheijang China 79 47 RCH IIB Hsiao…”
Section: Summary Of Search Results and Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…A US nationwide dataset derived from hospital episode statistics was also included covering 2377 procedures coded as colectomy for constipation indications [19]. Specific exclusions after full-text review (and after exclusion of non-English language publications: n = 10) included 27 studies where the population sample was confirmed to be less than 20 patients, four studies of out of scope procedures, one study where data were considered duplicate [13], one where outcomes could not be segregated by eligible procedure [14], and one where data for multiple clinical indications for colectomy were merged [15]. [27] 1995 Cleveland Clinic, FL USA 54 27 RCS IV Redmond [21] 1995 John Hopkins, Baltimore USA 34 90 PCH IIB de Graaf [28] 1996 Rotterdam Netherlands 42 46 PCH IV Lubowski [29] 1996 Sydney Australia 52 42 RCS IV Platell [30] 1996 Perth Australia 96 60 RCS IV Pluta [31] 1996 Alberta Canada 24 65 RCS IV Ghosh [32] 1996 Edinburgh UK 21 96 RCS IV Nyam [33] 1997 Singapore Singapore 74 56 PCH IV Ho [34] 1997 Singapore Singapore 24 24 RCH IV You [35] 1998 Taiwan China 40 24 PCS IV Bernini [36] 1998 Mayo Clinic, MN USA 106 78 RCH IV Hasegawa [37] 1999 Birmingham UK 61 84 RCH IV Fan [38] 2000 Taiwan China 24 23 RCS IV Pikarsky [39] 2001 Cleveland Clinic, FL USA 62 105 RCH IV Pikarsky [40] 2001 Cleveland Clinic, FL USA 30 60 PCS IV Webster & Dayton [41] 2001 Cancun Mexico 50 12 RCS IV Mollen [42] 2001 Bennekom Netherlands 21 62 PCS IV Nylund [43] 2001 Goteburg Sweden 40 132 PCS IV Lundin [44] 2002 Uppsala Sweden 28 50 PCS IV Fitzharris [45] 2003 Mayo Clinic, MN USA 75 47 RCS IV Hassan [46] 2006 Mayo Clinic, MN USA 104 68 RCH IV Marchesi [47] 2007 Parma Italy 23 72 PCS IV Zutshi [48] 2007 Cleveland Clinic, OH USA 69 130 RCS IV Feng [22] 2008 Zheijang China 79 47 RCH IIB Hsiao…”
Section: Summary Of Search Results and Study Qualitymentioning
confidence: 99%
“…Procedures considered beyond the scope of systematic review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] were: 1 Total colonic and rectal excision (proctocolectomy).…”
Section: Scopementioning
confidence: 99%
“…The first cases of subtotal colectomy with cecorectal anastomosis in multiple adenomas treatment were reported in 1962 by Rosi and Cahill [3]. Sarli et al [1] demonstrated that patients with inflammatory diseases and colon tumors could benefit from subtotal colectomies with ileocecal junction preservation. By the 4.5-year mean follow-up period, these patients had satisfactory results regarding frequency of bowel movements with 1.7 per day and normal stool consistency.…”
Section: Specificities Of Subtotal and Extended Left Colectomy In Thementioning
confidence: 99%
“…Extended hemicolectomies, as well as subtotal colectomies, are the possible options for salvage surgical treatment in specific clinical scenarios. These procedures were performed in patients with diverticulitis, Crohn's disease, transverse carcinoma, synchronous cancer, peritoneal carcinomatosis, previous sigmoidectomy, polyposis, and intractable constipation [1][2][3]. These approaches are considered to be preferable in these cases, as total colectomy can result in decreased reabsorption of water and electrolytes, ending up with diarrhea [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation